Preservation Of Local Food Culinary Lexicons Based On Social Status In The Indonesia–Timor Leste Border Area: A Socio-Econo-Ecolinguistic Analysis - Maria Magdalena Namok Nahak; Abdul Rahman Putera Dapubean; Kristofel Bere Nahak (MASI Mandiri Edukasi, 2026)
This study investigates the socio-econo-ecolinguistic dimensions of traditional culinary lexicons in Malaka Regency, a border area in eastern Indonesia. The research employs a qualitative descriptive design involving three social groups students, school pupils, and the general community as participants to capture intergenerational perspectives on traditional culinary knowledge. The study aims to (1) identify the linguistic forms of traditional culinary lexicons, (2) examine the dynamics of lexicon maintenance within local communities, and (3) analyze the socio-economic and ecological meanings embedded in traditional culinary practices. Data were obtained through field-based research methods, including community observation and documentation of local culinary terminology. The findings reveal sixteen traditional culinary lexicons: akar bilan, batar tasak, batar sonan, batar daan, batar tunun, batar faihedik, filun, fehuk tunun, fehuk sonan, fehuk hukus, fehuk daan, hudi tasak, hudi tunun, hudi daan, nunak, and es nu. These lexicons comprise basic and phrasal forms that convey cultural values, perform descriptive functions, and carry symbolic meanings rooted in local traditions. With regard to lexical vitality, the study indicates a weakening of intergenerational transmission, as younger generations, particularly students and pupils, demonstrate significantly lower levels of comprehension and use of traditional culinary lexicons than the general community, revealing a clear lexical gap. From a socio-economic perspective, the continued consumption of traditional foods contributes to local economic resilience by using locally sourced ingredients. Ecologically, these practices promote waste reduction, environmental preservation, and biodiversity conservation, while simultaneously supporting linguistic and cultural sustainability. Overall, the study highlights the importance of ecolinguistic awareness in sustaining the vitality of traditional culinary lexicons as an integral component of cultural identity and environmental ethics.